Corrigendum to "The role of calcitonin receptor signalling in polyethylene particle-induced osteolysis" [Acta Biomater. 14 (2015) 125–132]. (1st September 2015) - Neuerburg, Carl; Wedemeyer, Christian; Goedel, Jan; Schlepper, Rüdiger; Hilken, Gero; Schwindenhammer, Benjamin; Schilling, Arndt Friedrich; Jäger, Marcus; Kauther, Max Daniel
Graphical abstract: